2006
DOI: 10.4049/jimmunol.177.6.3960
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Alters Localization of MHC Class II and Dendrite Morphology in Mature Langerhans Cells

Abstract: Hemopoietic stem cell-derived mature Langerhans-type dendritic cells (LC) are susceptible to productive infection by human CMV (HCMV). To investigate the impact of infection on this cell type, we examined HLA-DR biosynthesis and trafficking in mature LC cultures exposed to HCMV. We found decreased surface HLA-DR levels in viral Ag-positive as well as in Ag-negative mature LC. Inhibition of HLA-DR was independent of expression of unique short US2-US11 region gene products by HCMV. Indeed, exposure to UV-inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 63 publications
3
42
0
Order By: Relevance
“…The efficacy of inactivation was tested by immunofluorescence staining of MRC5 cells infected with UV-HCMV using anti-immediate-early antigens (IEAs) monoclonal antibody (MAb) and pp65 MAb (see below), followed by a secondary fluorescein isothiocyanate (FITC)-conjugated goat anti-mouse antibody (data not shown). Successful inactivation was ensured through abrogation of IE antigen expression, whereas pp65 tegument protein detection was comparable to cell infection with nonirradiated virus by using methods previously described (13,34).…”
Section: Cells and Virusmentioning
confidence: 99%
“…The efficacy of inactivation was tested by immunofluorescence staining of MRC5 cells infected with UV-HCMV using anti-immediate-early antigens (IEAs) monoclonal antibody (MAb) and pp65 MAb (see below), followed by a secondary fluorescein isothiocyanate (FITC)-conjugated goat anti-mouse antibody (data not shown). Successful inactivation was ensured through abrogation of IE antigen expression, whereas pp65 tegument protein detection was comparable to cell infection with nonirradiated virus by using methods previously described (13,34).…”
Section: Cells and Virusmentioning
confidence: 99%
“…Mechanisms are targeted to various steps within the same pathway, presumably leading to greater efficiency. For example, inhibition of constitutive MHC II expression, which results in decreased CD4 ϩ T cell recognition, has been reported to result from altered localization of constitutive MHC II (23)(24)(25). Other mechanisms have involved either degradation or inhibition of assembly of MHC II by US2 and US3 proteins (26).…”
Section: Inhibition Of Ifn-␥-mentioning
confidence: 99%
“…Maturation of DCs leads to phenotypic changes including upregulation of the costimulatory and adhesion molecules CD40, CD80, CD83, and CD86, which are involved in T-lymphocyte activation, and increased MHC-I and -II expression on the surface of maturing DCs (3,43,62). A number of studies have demonstrated that productive HCMV infection interferes with the maturation of DCs and their antigen-presenting function by inhibiting the expression of these immune molecules (4,18,30,38,51). Furthermore, Chang et al (9) and Raftery et al (46) showed that stimulation of immature DCs to mature in the presence of cmvIL-10 results in the functional paralysis of DCs (9,46).…”
mentioning
confidence: 99%